Restorative Justice terhadap Korban Tindak Pidana Kekerasan Seksual di Indonesia: Analisis Perpol No. 8 Tahun 2021 dan Studi Kasus Karawang - Busyra Salsabila; Anita Zulfiani; Riska Andi Fitriono (Indonesian Publication Center, 2026)
This research examines the regulation of restorative justice under National Police Regulation (Perpol) No. 8 of 2021 on Handling Criminal Acts Based on Restorative Justice, and its implementation in a sexual violence case in Karawang. This research is motivated by the disharmony between Perpol No. 8 of 2021, Law No. 12 of 2022 on Sexual Violence Crime, and Law No. 20 of 2025 on the New Code of Criminal Procedure, which creates a legal loophole allowing sexual violence cases to be resolved through a deviant application of restorative justice. This research employs a normative-empirical legal method with a descriptive character using case, statutory, and sociological approaches. Primary legal materials were obtained through interviews with the victim's legal counsel, while secondary legal materials were gathered through literature study. The analysis was conducted using Aristotle's theory of justice and Lawrence M. Friedman's theory of legal certainty. The findings show that Perpol No. 8 of 2021 does not include sexual violence among criminal offenses excluded from restorative justice, contradicting Article 23 of the Sexual Violence Crime Law and Article 82 point (d) of the new Criminal Procedure Code. The application in Karawang was carried out through forced unregistered marriage without investigation, official case registration, or special case review, violating Perpol, the Sexual Violence Crime Law, and the new Criminal Procedure Code simultaneously. From Aristotle's theory of justice, this failed to achieve distributive or corrective justice. From Friedman's theory of legal certainty, uncertainty stems from weaknesses in legal substance, legal structure, and legal culture.